Successful use of docetaxel for emergency treatment of disseminated intravascular coagulation due to hormone-refractory metastatic prostate cancer - Serkan Keskin; Meltem Ekenel; Mert Başaran; Sevil Bavbek (Journal of Oncological Sciences, 2017)
Disseminated intravascular coagulation (DIC) is a fatal presentation of metastatic adenocarcinoma of the prostate. A 59-year old male presented with a 2-week history of fatigue, red urine, and bruises on his body. Physical examination and ultrasonography showed that the patient had an enlarged prostate. Laboratory analysis was consistent with DIC. The patient's PSA level was 90 ng mL−1. Bone scintigraphy showed diffuse metastasis. Histopathological analysis of a biopsy specimen showed prostate adenocarcinoma. Acute DIC improved rapidly following initiation of leuprolide and bicalutamide hormone therapy. The patient's PSA dropped from 90 to 0.01 ng mL−1 after 1 month of treatment. The patient had recurrence of the initial complaints and elevated PSA while receiving leuprolide treatment in first year. As the patient's clinical condition deteriorated, we initiated docetaxel-containing chemotherapy. The patient's symptoms became less severe and his abnormal laboratory findings began to normalize after 2 weeks of the chemotherapy, and they completely resolved returned to normal after 2 months. In conclusion, docetaxel-containing chemotherapy in a patient with metastatic prostatic carcinoma and DIC was effective, despite a low platelet count and bleeding.